(untitled) (Global Journal of Medical Research, 2023)
Small intestinal diverticulosis is very rare The incidence ranges from 0 06 to 1 3 with a higher prevalence after the 6th decade of life Among these small intestinal diverticula duodenal diverticulosis is more frequent followed by diverticula of the jejunum and ileum 1 Jejunal diverticulosis is a very rare disease It is usually asymptomatic or associated with non-specific symptoms which makes the diagnosis more challenging 2 When present they are usually multiple and located in the proximal jejunum Rarely they can cause acute complications that can develop into an acute abdomen requiring surgical intervention 3 Here we describe a case of complicated isolated jejunal diverticula with perforation which was successfully treated with resection and anastomosis of the defective segment